Pengaruh Karakteristik Auditor Terhadap Audit Report Lag - Awin Saputra Daulay; Vanica Serly (Universitas Negeri Padang, 2020)
This study is intended to prove empirically the effect of Auditor Characteristics on Lag Audit Reports. This research is classified as quantitative research with a causative approach. The population in this study is financial sector companies listed on the Indonesia Stock Exchange in 2014-2018. The purposive sampling method is used, so there are 61 financial sector companies obtained as a sample in year 2014-2018. The type of data is secondary data obtained from www.idx.co.id. The analytical method used is multiple linear analysis.The results of this study indicate that (1) The auditor's reputation has a negative and not significant effect on audit report lag (2) Audit tenure has a positive and not significant effect on audit report lag (3) The auditor industry specialization has a positive and not significant effect on audit report lag (4) Auditor switching has a positive and not significant effect on audit report lag.